O feito & o olhado: Performances da aflição e a liturgia popular dos corpos em afecção. - Araújo, Fabiano Lucena de (2015)
This study aims to present manifestos ritual relationship modes in the contexts of therapeutic agencies of afflictions, with the popular religiosity backdrop, and the specific focus of benzeção in popular Catholicism and religions of African origin. The construction of argumentative process tries to sketch a performative way of afflictions from flows of the surveyed interlocutors and inserting ways in the religious field specified above, the ritual plan for healing and solving everyday problems. The prospect of performance driven agency to analyze the afflictions have as reference the schema on the ritual function of transformation and transport system, prepared by Richard Schechner, which speaks to the formulation of Victor Turner about the corpus Ritual Ndembu - Affliction ritual / Initiation ritual. The discursive regimes or ritual experience called fetish ("feito") and eyed ("olhado") translate an elementary differentiation as to i) notion of body and person, ii) nature and etiology of affliction (etiological model) and iii) procedures for the treatment of affliction (therapeutic model). The transportation-transforming Richard Schechner system gives opportunity to identify two fundamental analysis tracks for engagement modes of subjects addressed in the context of therapeutic agency: i) A differentiation of conscious ways of relating with the action a "concentration gradient [in ] and control, ritual context of domain "and II) that experts healers, considered here, offer experiential rearrangement proposals from the reorganization or reclassification of experienced by subjects in a specific scenario proposed to them, for liturgies or public services dressings; ie, there is a strong link between liturgy and drama (-turgy), as predicted Victor Turner.